Florencia y Bagdad : una historia de la mirada entre Oriente y Occidente - Belting, Hans; Chamorro Mielke, Joaquín; Belting, Hans. (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2012)
In this illustrated study, Belting deals with the double history of perspective, as a visual theory based on geometrical abstraction (in the Middle East) and as pictorial theory (in Europe). Florence and Baghdad addresses a provocative question that reaches beyond the realm of aesthetics and mathematics: What happens when Muslims and Christians look upon each other and find their way of viewing the world transformed as a result?
La perspectiva y la cuestión de las imágenes : caminos entre Oriente y Occidente. -- El ojo sometido : la crítica de la mirada en el islam. -- La medición de la luz por alhacén : la invención árabe de la camera obscura. -- La percepción como conocimiento : la transformación de la teoría de la visión en teoría de la imagen. -- La medición de la mirada por Brunelleschi : la perspectiva matemática y el teatro. -- EL sujeto en la imagen : la perspectiva como forma simbólica.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed April 29, 2016)
Keywords: Perspective -- History; Art, Renaissance -- Islamic influences; Aesthetics, Comparative; Optics -- Islamic countries -- History; Electronic books